Farm-to-table via collection centres in Fiji - Tuqa, Alisi; Lobendahn, Kristyn; Bainivalu, Sema (Technical Centre for Agricultural and Rural Cooperation, 2018)
Every year, €215 million worth of fruits and vegetables are imported to Fiji, mostly to supply the local restaurant and hotel industry. In 2016, the Pacific Islands Private Sector Organisation (PIPSO) launched a project to address the challenges faced by Fijian farmers and to establish agricultural collection centres to improve the amount of ‘farm-to-table’ produce used in the country’s tourism sector.